Punishment for Perpetrators and Performers of Immoral Acts in the Perspective of Islamic Criminal Law (Fiqh Jinayah) - Aulia, Puja; Alfarizi, Muhammad Fadil; Rambe, Khairul Mufti (Al-Qanun: Jurnal Kajian Sosial dan Hukum Islam, 2022)
Casual sex is now an "industry" with legal and illegal locations, and is no longer just an individual act. Many perpetrators are involved in this, such as pimps, sex brokers, venue providers, delivery men, and others. Apart from the perpetrators of adultery themselves, they can also be called facilitators of adultery or obscene acts. This study aims to determine the perspective of jinayah fiqh regarding facilitators of immoral acts and the sanctions given to them. This research shows that those who provide facilities for immoral acts are included in the jarimah category in Jinayah fiqh and included in the jarimah ta'zir category using content analysis methods and a juridical-normative approach to various qualitative data. Facilitators of this obscene act will receive ta'zir sanctions, and the severity or lightness of the punishment will be the right of the State in accordance with the demands of public welfare.